Open your eyes: poetic rhythm and linguistic aspects in signed poetry - Sampedro Terron, Miguel Ángel (Tropelías: Review of Literary Theory and Comparative Literature, 2023)
The poetic dimension of sign languages (SL) is a rather unknown case in Spain, as well as in many other countries. This article presents the main linguistic aspects of SL and their linguistic influence on the conformation of poetry, comparing them with those of oral poetry. About the general poetry, it seems necessary to ask the question of the theoretical problem of poetry. This idea is associated with phonocentrism, an idea of wich Derrida speaks in depth in his studies. This author refers to the need to deconstruct the concept of poetry as an essential part of global poetry due to its null sonority. This study shows that poetic rhythm is no longer an exlusive concept of oral languages and, likewise, allows us to understand how poetry works without phony in SL.